Impact of exposing lithium metal to monocrystalline vertical silicon nanowires for lithium-ion microbatteries - Refino, Andam Deatama (2024)
Silicon has attracted considerable attention for use as high-capacity anodes of lithium-ion microbatteries. However, its extreme volume change upon (de-)lithiation still poses a challenge for adoption as it leads to severe active lithium loss that shortens the cycle life. Here, we fabricate three-dimensional monocrystalline vertical silicon nanowires on a silicon wafer using low-cost metal-assisted chemical etching, then cover them with lithium using thermal evaporation prior to the battery operation as the pre-lithiation step, to investigate its impact on electrochemical performance. To reveal the underlying physical and electrochemical mechanisms, we also process a comparative planar monocrystalline silicon. We find that pre-lithiation results in improved (de-)lithiation behavior, especially in planar silicon-based cells, while silicon nanowire-based cells exhibit low capacity in early cycles. This study sheds light on the surface design and structural modification of monocrystalline silicon nanowires with respect to pre-lithiation by lithium thermal evaporation.